Social and Cultural History of Indonesia: Narratives of Identity, Tradition, and Transformation - Rosmaria Rosmaria (Archipel: Journal of Indonesian Interdisciplinary Studies, 2025)
This article examines the social and cultural history of Indonesia by tracing the dynamic relationship between identity, tradition, and transformation from the colonial period to the present. Using a multidisciplinary historiographical approach, it analyzes literature, oral traditions, and cultural practices that reveal Indonesia’s diverse historical trajectory. The discussion highlights how colonial encounters restructured social organization while encouraging hybrid cultural forms; how oral traditions and ritual performances safeguarded linguistic and communal identities; and how modernization, urbanization, and globalization have introduced both opportunities and tensions in maintaining heritage. Religion emerges as a unifying force that reinforces solidarity across Indonesia’s plural society, while collective memory and cultural nationalism continue to negotiate the balance between national unity and regional diversity. By foregrounding these cultural dimensions, the study demonstrates that Indonesia’s historical narrative is not merely political or economic but deeply rooted in lived experiences, enabling the nation to preserve and adapt its identity in an era of constant change.